Employee motivation in facing challenges in the insurance industry with the role of creativity as a key factor: case study of Madura BPJS Employment - Aisyah, Siti; Anshori, M Isa (Journal of Business Management and Economic Development, 2024)
Challenges in the insurance industry require companies to prepare strategic steps with various tasks and responsibilities assigned to their employees. Employee motivation is needed to face various possibilities that arise from these challenges. BPJS Employment Madura is a public legal entity responsible to the president which is able to provide benefits to increase the nation's economic growth which is currently facing challenges in the insurance industry. The aim of this research is to analyze the work motivation shown by employees with creativity as a key factor in facing the challenges of the insurance industry. The method for writing scientific articles is using qualitative research methods and data collection techniques in the form of interviews and observations. This research activity explains the work motivation of BPJS Employment Madura employees in facing the challenges of the insurance industry with creativity to solve various problems that arise so that they can achieve company goals.